Tree Growth Under Climate Change: Evidence From Xylogenesis Timings and Kinetics - Vieira, Joana; Carvalho, Ana; Campelo, Filipe (Frontiers in Plant Science, 2020)
Tree growth is one of the most studied aspects of tree biology, particularly secondary growth. In the Mediterranean region, cambial activity is mostly determined by water availability. Climatic projections for the Mediterranean region predict more frequent and intense droughts, and longer periods without precipitation. To investigate tree growth under the predicted scenarios of climate change, a water manipulation experiment was conducted in a maritime pine stand (Pinus pinaster Aiton). In 2017, fifteen trees were divided into three groups: control, rain exclusion, and irrigation. Drought conditions were simulated by installing a continuous plastic sheet on the forest floor from March to September. Trees under irrigation treatment were watered twice a week in September. Cambial activity and xylem formation was monitored every 10 days from February 2017 until March 2018. Cell production was maximal around the spring equinox in all treatments. Trees under rain exclusion decreased cell production rates, xylogenesis duration, and latewood cell wall thickness. The extra irrigation in September did not produce noticeable differences in xylogenesis compared to trees in the control treatment. The synchronization of maximum cambial division rates around the vernal equinox (spring) could allow Mediterranean trees to mitigate the impact of summer drought. With the predicted increase in drought intensity and frequency, lower tree productivity, carbon sequestration, and wood biomass are expected.